Why is there a gap between attitudes and behaviours toward healthy eating in low income households in the UK; what action can be taken in an effort to reduce negative attitudes and increase healthier purchasing behaviour? - orme, H.J. (2013)
Background Throughout the literature it has been established that there is a gap between attitudes and behaviours toward healthy eating, in particular this is stressed in low income households, who eat a significantly poorer diet than high income households. The health complications, increasing rates of obesity and socioeconomic inequalities in health have become a large concern for health professionals and researchers. Thus many studies have tried to gain an understanding of the reasons for this and provide a number of solutions in order to encourage healthy eating in low income groups. Price, access, education and environment as well as differences in gender and lifestyle choices such as smoking have all been considered, however not equally. Objectives This research project aims to address the issue of poor diets common in low income groups in an attempt to uncover any new information explaining why this is the case and potentially provide some realistic solutions that may change this behaviour and reduce negative attitudes to healthy eating. A heavier focus will be on knowledge and understanding of healthy eating, which has not been reviewed in the literature as often as other factors such as price. The proposed research questions which I hope to answer are as follows; RQ1: What are the perceived barriers and promoters of eating healthily? RQ2: Is there a lack of knowledge surrounding healthy eating and does this prevent people making healthy purchasing decisions? RQ3: What, if anything, could be done to reduce the perceived barriers and change behaviours? Method A total of ten in depth semi structured interviews were used in order to gain the relevant information. Participants were selected primarily through purposeful sampling, to ensure that they were within the low income bracket that was needed for the study. From these initial participants snowball sampling was used as participants identified others that they believed would be willing to participate. Questions asked covered four main areas; promoters, barriers, knowledge and motivation to change and interviews were conducted until saturation occurred. Interviews lasted around twenty minutes and were recorded, transcribed and analysed through thematic analysis, whereby themes and categories were outlined from the responses and then compared. Results 90% of the participants believed that they consumed a healthy diet, yet only 10% ate the recommended five portions of fruit and vegetables per day. 60% of participants were in agreement that price and preference were issues preventing them from eating healthier. Whilst 40% considered time to be an influencing factor, contrary to studies in the literature access was not a problem for this group of participants. The largest promoter for not eating healthily was the taste of unhealthy options (80%) which was considered a more appealing option for other reasons as well such as price (40%) in comparison to healthy alternatives and the convenience and ease of eating it (60%). Knowledge among the participants was low, with only 50% utilising nutritional labels; 40% used them for calorie controlled diets to lose weight, yet only 10% knew what a calorie was. 40% believed that educating the population would increase healthier purchases, whilst the rest believed that lowering the price of healthy foods would alter behaviour and 30% would not be willing to change their eating habits regardless. Furthermore access to a car and smoking did not impact attitudes toward healthy eating. Conclusion Price and convenience were both considered barriers to eating a healthy diet; however taste and preference were the most influential factors. People generally preferred the taste of unhealthy options such as fast foods and found them more convenient. Cravings emerged as a driving force for consuming unhealthy foods, which supports the idea that they are addictive and not necessarily a choice for some people. This is enhanced by deceitful adverts encouraging temptation, the cheapness of the foods in comparison to healthy alternatives and misleading nutritional labels. Many people were lacking knowledge surrounding a healthy diet; they did not know what they should be consuming and why. Thus efforts could be made to increase the prices of unhealthy foods through taxes and to educate people about the risks and benefits of diet.